ANALISIS KINERJA GURU PADA SEKOLAH MENENGAH ATAS NEGERI 01 KARAMAT KABUPATEN BUOL - Sondeng, Ahmad (STISIPOL Mujahidin Buol, 2022)
This research aims to determine the performance of teachers at the principal of SMA Negeri 01 Karamat, Buol Regency. The research method used is a quantitative research method using descriptive analysis, population and samples, and research procedures using observation, interviews, and questionnaires. The research results show that in general the results obtained are that teacher performance, which includes the dimensions of teacher performance in learning planning, teacher performance in implementing learning, teacher performance in learning evaluation, teacher performance in learning evaluation, and teacher performance in task discipline, is good. In general, the performance of teachers at State High School 01 Karamat, Buol Regency is quite good because the results achieved by teachers at the school in planning, implementing, evaluating, and disciplining their duties are by the responsibilities that exist in their abilities towards a profession that has value or achievement results. Work. In general, the results or work performance scores are the result of teachers' performance in carrying out their duties so that they can achieve fairly good and efficient results.